IC 8566 Economic Availability Of Byproduct Fluorine In The United States 1.Utilization Of Byproduct Fluosilicic Acid In The Manufacture Of Aluminum Fluoride 2.Utilization Of Byproduct Fluosilicic Acid In The Manufacture Of Calcium Fluoride - Robert C. Johnson (The National Institute for Occupational Safety and Health (NIOSH), 1973)
Domestic byproduct fluorine (in fluosilicic acid) availability at various price levels of aluminum fluoride were determined and a contingency availability curve developed. The supply of byproduct fluosilicic acid is restricted in amount to certain geographic regions, where plants processing phosphate rock are located, and the byproduct can be collected. The maximum possible U.S. annual supply, based on potential plant capacities, is 373,400 tons of fluosilicic acid containing 295,400 tons of fluorine. Based on inputs of 5, la, 25, 50, and 100 thousand tons per year, five levels of producing aluminum fluoride from fluosilicic acid (100 percent) were costed. Based on a 12-percent discounted cash flow rate, including the cost of salvaging the fluosilicic acid, the calculated selling price of aluminum fluoride ranged from $233 per ton to $448 per ton. At the higher price, 98 percent of the potential supply of byproduct fluosilicic acid could be used profitably; at the lower price only 46 percent could be used profitably.